MXenes: Emerging 2D materials for hydrogen storage. (July 2021) - Kumar, Pradip; Singh, Shiv; Hashmi, S.A.R.; Kim, Ki-Hyun
Abstract: The generation of sustainable energy has become a priority issue to properly maintain the sustainability of humankind. To meet the future global energy demands, the efficient generation of clean and renewable energy like hydrogen has become the need of the hour. Currently, hydrogen is being used either as a compressed gas in high-pressure tanks or in liquefied form in tanks. However, these storage technologies have safety issues, making the solid-state storage approach an attractive alternative option. In this context, the potential of light-weight high-performance solid-state materials like MXenes (a few-atoms-thick layers of transition metal carbides, nitrides, or carbonitrides) allow reversible hydrogen storage. The Ti2 C MXene has shown a maximum hydrogen adsorption capacity up to 8.6 wt%, which is far higher than the gravimetric capacity of metal-based complex hydrides ( 5.5 wt%) as set by U.S. DOE (2015). Hydrogen storage performance was also evaluated in other MXenes like Ti3 C2, Cr2 C, Ti2 N, and their composites. Despite their great potential, the utility of MXenes in hydrogen storage applications has not been explored to its full extent. In this review, a detailed discussion is provided on state of art applications of MXene-based materials for hydrogen storage along with their challenges and future outlook. Graphical Abstract: ga1 Highlights: There is a growing demand for renewable energy like H2 to break the dependence on fossil fuels. The potential of 2D materials for hydrogen storage is recognized due to their multiple merits. The utility of MXene-based materials is high due to their superior capacities for storage. A review is given to describe their synthesis, performance evaluation, and future potential.